Hot rolling of binary Ti-Nb alloys Part II: Mechanical properties anisotropy - Banumathy S.; Mandal R.K.; Singh A.K. (My University, 2025)
This work describes the nature of anisotropy in mechanical properties of three alloys, namely Ti-8Nb, Ti-12Nb and Ti-16Nb in the hot rolled condition. The work hardening curves of the alloys Ti-8Nb and Ti-12Nb exhibit a single slope and follow the Ludwik relation. The alloy Ti-16Nb displays two slopes in work hardening curves. This indicates that two different mechanisms are operative during tensile testing. The work hardening curves follow a modified Ludwik equation. The alloy Ti-16Nb exhibits the lowest anisotropy index and percentage in plane anisotropy. The alloy Ti-12Nb exhibits the highest values of both the anisotropy index and percentage in plane anisotropy. The low percentage in plane anisotropy of the alloy Ti-16Nb has been attributed to the presence of fibre textures. The yield loci of the hot rolled alloys have been determined using the Knoop hardness method. The results show that hot rolling induces anisotropy in yield strength and changes the shape and size of yield locus plots. © 2011 Carl Hanser Verlag, Munich, Germany.